(untitled)
bl ’kks/k i= esa 11&14 uoEcj 2008 ds nkSjku caxky dh [kkM+h esa cuus vkSj mlds vkxs c<+us okys m".kdfVca/kh; pØokr dSeqd dh xfrdh; fLFkfr;ksa ds fo’kys"k.k ij fopkj&foe’kZ fd;k x;k tks fupys Lrj ij ifjofrZr ok;qnkc&m".kdfVca/k ¼csjksVªkfid½ mtkZ ij dsfUnzr FkkA bl nkSjku ;g ik;k x;k fd if’peh iz’kkar egklkxj ls miks".kh; iwohZ gok;sa e/; caxky dh [kkM+h ds mRrj rd c<+h vkSj Åij m)`r vof/k esa Hkwe/;js[kh; if’peh gok;sa ¼iNok¡½ vkbZ-Vh-lh-tsM+- ds nfk.k rd c<+h ftlds dkj.k kSfrt; vi:i.k izokg vR;kf/kd ek=k esa cukA blls pØokrh vi:i.k Hkzfeyrk mRiUu gqbZ vkSj fokksHk cuk] tks ckn esa m".kdfVca/kh; pØokr dSeqd esa fodflr gks x;kA fupys kksHkeaM+y esa ewyHkwr ks=h; izokg ok;qnkcm".kdfVca/k :i ls vfLFkj Fkk ftls fujisk Hkzfeyrk ds ;kE;ksrjh forj.k ds yk.k ds ifjorZu kjk crk;k x;k gS ftlls coaMj ds cuus esa xfrdh; ÅtkZ feyhA bl nkSjku fujisk Hkzfeyrk ds ek/; ks=h; izokg vkSj ;kE;ksrjh izo.krk ds chp ldkjkRed lglaca/k Fkk ftlls ok;qnkcm".kdfVca/k kjk coaMj ek/; izokg dh vUrjfØ;kvksa ds kjk coaM+j dh xfrdh; ÅtkZ esa o`f) gqbZA ÅtZLoh fo’ys"k.k ls irk pyk gS fd coaM+j okyh xfrdh; ÅtkZ ds ldkjkRed ifjorZu ds mPp nj ds ks= ifjorhZ ok;qnkc m".kdfVca/k ds ldkjkRed ks=ksa ls esy [kkrs gSa vkSj ifjorhZ m".kdfVca/k ds ifjek.k Hkzfey mRifRr okys ks= ds vkl&ikl coaM+j okyh xfrdh; ÅtkZ ds ifjorZu ds LFkkuh; le; ds lkFk esy [kkrs gaSA ewyHkwr ks=h; izokg ds ;kE;ksrjh vi:i.k kjk ifjofrZr ok;qnkc m".kdfVca/k ÅtkZ m".kdfVca/kh; pØokr dSeqd ds cuus vkSj mlds vkxs c<+us okys ,d egRoiw.kZ ÅtkZ L=ksr FkkA Analysis of dynamical conditions in respect of formation and growth of tropical cyclone Khai Muk over the Bay of Bengal during 11-14 November 2008 is discussed with focus on barotropic energy conversion at lower level. It is observed that the extension of subtropical easterlies from the Western Pacific in to central Bay of Bengal to the north and equatorial westerlies to the south of ITCZ during the above period constituted a large scale horizontal shear flow. This led to generation of cyclonic shear vorticity and initiation of disturbance which later developed in to tropical cyclone Khai Muk. The basic zonal flow in the lower troposphere was barotropically unstable as depicted by change of sign of meridional distribution of absolute vorticity which provided the kinetic energy for the growth of eddy. There existed positive correlation between mean zonal flow and the meridional gradient of absolute vorticity which favoured increase of eddy kinetic energy through barotropic eddy-mean flow interactions. Energetic analysis indicated that areas of high rate of positive change of eddy kinetic energy coincided with positive areas of barotropic conversion and the magnitude of barotropic conversion matched with local rate of change of eddy kinetic energy around the area of vortex generation. Barotropic energy conversion by meridional shear of basic zonal flow was an important energy source for the formation and initial growth of tropical cyclone Khai Muk. , number=1, journal=MAUSAM, year=2013, month=Jan., pages=49–58